The role of the Catholic Church in Jakarta in a Pluralistic Society: Contributions, Challenges, and Prospects - Resta Agustiani; Desy Safitri; Sujarwo (PT. Intelek Cendikiawan Nusantara, 2024)
Tolerance is the primary capital in relationships between religious groups in order to create a harmonious life. The study was conducted to identify the activities of the Catholic Church in Jakarta, which participated in promoting tolerance among religious groups. Data collection in this research uses the study of literature using scientific journals, books, archives, and documents related to the research. As for the routine activities of the Catholic Church in creating tolerance in the sphere of plural societies, they routinely conduct cross-religious dialogue in order to create a sense of unity. This activity is carried out by many religious leaders and young generations in the hope of fostering religious tolerance in the midst of plural societies